Study of clinical profile of stroke patients in rural tertiary health care centre - Patne, Sanjay V.; Chintale, Kailas N. (International Journal of Advances in Medicine, 2016)
Background: There are 15 million people worldwide who suffer a stroke each year. According to the World Health Organization, stroke is the second leading cause of death for people above the age of 60 years, and the fifth leading cause in people aged 15 to 59 years old. Each year, nearly six million people worldwide die from stroke. One in six people worldwide will have a stroke in their lifetime. Methods: This cross sectional study was carried out from July 2014 to April 2016 of all new patients admitted with stroke in Indian institute of Medical Sciences and Research Center, Badnapur, Jalna, Maharashtra. India. Results: The cerebrovascular strokes were more common in males (58.53%) than females (41.46%). Most common age group was 61-70 years (34.95%). The Most common clinical feature was Hemiplegia (55.28%). most common risk factor was hypertension (48.78%), tobacco chewing (26.01%), smoking (19.51%), followed by past h/o of cerebrovascular stroke (12.19%), Dyslipidemia (8.94%). Most common type of stroke was ischemic (68.28%) and hemorrhagic (31.69%) was second most common in ischemic strokes most common involved areas were parietal (30.08%), basal ganglia (9.75%), frontal lobe (7.31%). In hemorrhagic stroke most common site was thalamus (10.56%) followed by ventricular (5.69%) and basal ganglia (4.06%). Conclusions: Young patients (age ≤45 years) were 16.26% which is more dangerous in view of productive year lost. Stroke having male predominance with hypertension was the most common risk factor smoking tobacco chewing and dyslipidemia were other risk factors for stroke and most common type of stroke was ischemic. Developing countries like India are facing a double burden of communicable and non-communicable diseases. Stroke is one of the leading causes of death and disability in India.